Resíduo de quinolonas em músculo, fígado e rins de frangos e influência do material fecal na resistência antimicrobiana de Salmonella spp - Zonatto, Fernanda (2020)
In the broiler production chain, antimicrobials are used to treat infectious diseases and as growth promoters. The inappropriate use of antibiotics can accumulate residues in the carcass and transfer resistant strains in the food chain. The objective of this work was to evaluate the presence of antibiotic residues in muscle, liver and kidneys of chickens by creating 120 broilers (Cobb) in experimental farm. For this, the chickens were medicated for 5 consecutive days, the treatments were applied orally in the drinking water, being: A) drinking water (control) and B) enrofloxacin (10 mg/kg). After treatment, the animals were euthanized and samples of muscle, kidneys and liver were collected. The quantification of residues was performed by liquid chromatography coupled to a mass spectrometer, after standardization and validation of the methodology. The validation was performed through the parameters of linearity, selectivity, precision, accuracy, detection limit and quantification limit. In addition, the influence of fecal material on the antimicrobial resistance of Salmonella spp. was evaluated, as well as residues of enrofloxacin (ENR) and ciprofloxacin (CIP) of muscle and viscera of poultry. For that, samples of chicken faeces were collected from different producers, and the resistance of Salmonella spp. was evaluated for commercial antimicrobials, associated with microorganisms present in the gastrointestinal microbiota of chickens. For this study, the techniques of contact with antimicrobials and disk-diffusion were used. As a result there is a methodology for analysis of sensitive and viable ENR and CIP for industrial application, with LQ of 10 μg/kg, LD of 20 μg/kg, recovery rates of 92.47%-100.91% for ENR and 89.36%-8.33% for CIP for muscle, liver and kidney. It was defined with depletion tests for commercial antimicrobials 3 days to reduce the concentration of waste below the maximum residue limit (MRL) and thus minimize the problem associated with resistance. In addition, there was a reduction in the sensitivity of ENR to Salmonella spp. associated with fecal material and resistance to three different classes of tested antimicrobials, indicating the presence of multidrug resistance. The appearance and spread of Salmonella spp. resistant to antimicrobials, as well as the presence of residues, has important public health implications and should be constantly monitored.